The administrative judiciary reforms in Ukraine - Zuieva, Larysa (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The history of the establishment of administrative judiciary in Ukraine dates back to the 19<span class="Indeks-G-rny char-style-override-5" style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">th<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> century, but only after regaining independence did the process of its development begin. Administrative courts have only been envisaged in the Ukrainian Constitution as independent judicial organs since 2016, and the current system of these courts includes: the Supreme Court, appellate courts and district administrative courts. Proceedings before administrative courts are governed by the Code of Administrative Judiciary of Ukraine of 2005. The aim of the study is to present the challenges facing the Ukrainian administrative judiciary and to formulate postulates aimed at improving its functioning. The most important of these include ensuring the uniformity of the case law of the Supreme Court and modernizing the provisions on administrative proceedings.